Diaspora Rohingya dan Tantangan Adaptasi Budaya di Negara-Negara Penerima - Yohanis Kristianus Tampani; Julita Fuka; Leonarda Luisa Seran; Ikson Banfatin; Kornelia Tsu; Lusiana Mali; Adrianus Berek (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
This study aims to explain the Rohingya diaspora and the challenges of cultural adaptation in host countries. This study uses a library research method where data collection in this study uses various materials and materials available in libraries such as books, scientific articles/journals, and documents that are relevant to the research topic. The results of the study show that the state of Myanmar through the Burma Citizenship Law 1982 policy has designated only 135 ethnicities recognized as its citizens and the Rohingya ethnic group is not included in it. As a result, they legally lose their citizenship status (stateless), rights to land, education, employment, and a decent life. Lacking legal legitimacy makes the Rohingya ethnic group trapped in a cycle of discrimination and poverty. Therefore, in search of a decent life, the Rohingya ethnic group migrates to seek new asylum to neighboring countries such as Bangladesh, Thailand, and Indonesia in the hope of getting a decent living. In refugee camps, a process of cultural acculturation occurs where as a group of immigrants (the Rohingya ethnic group) must get used to accepting and adapting to the new environment, culture, and lifestyle without forgetting their identity as the Rohingya ethnic group.